Pengujian Black Box Menggunakan Metode Cause Effect Relationship Testing - Nadya Safitri; Rully Pramudita (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2018)
Abstrak: Pengujian merupakan sebuah tahapan yang dilakukan oleh tester untuk menemukan kesalahan yang ada di suatu perangkat lunak. Salah satu teknik testing yang sering digunakan yaitu black box testing. Pada penelitian ini akan dicoba menerapkan teknik black box testing. Teknik black box testing terdiri dari beberapa cara, yaitu Equivalence Partitioning, Boundary Value Analysis / Limit Testing, Comparison Testing, Sample Testing, Robustness Testing, Behavior Testing, Requirement Testing, Performance Testing, Endurance Testing, Cause-Effect Relationship Testing.Cause Effect Relationship merupakan cara pengujian dengan melakukan ujicoba yang dilakukan berdasarkan kondisi logikal dan aksi yang berhubungan. Hasil pengujian ini memberikan kesimpulan mengenai kebenaran fungsi dari aplikasi yang diuji serta apa saja kesalahan yang masih terdapat didalamnya. Kata kunci: Aplikasi, Black Box, Cause, Effect, Pengujian Abstract: Testing is the stage carried out by the tester to find errors that exist in the software. One testing technique that is often used is black box testing. In this study we will try to apply the black box testing technique. Black box testing techniques consist of several ways, namely Equivalence Partitioning, Boundary Value Analysis / Boundary Testing, Comparative Testing, Sample Testing, Robustness Testing, Behavioral Testing, Needs Testing, Performance Testing, Durability Testing, Testing of Cause and Effect Relations. how to test by conducting tests based on logical conditions and related actions. The results of this test provide conclusions about the functions of the applications that support and what is still in it. Keywords: Application, Black box, Cause, Effect,Testing